Is the Video Game a Cultural Vehicle? - Chen, Chi-Ying (Games and Culture, 2013)
Following the exportation of Japanese media products such as TV dramas, Japanese culture and products have swept across many Asian countries, especially Taiwan. Based on the historical background and unique characteristics of games, this study investigates the cultural effect of Japanese video games on players in Taiwan. This study also presents an analysis of the differences between TV and the video game as cultural vehicles. We used both quantitative and qualitative methods. Results indicate a relationship between game-playing behavior and the identification of Japanese culture. However, the relationship between video game playing and consumption was nonsignificant. This shows the power of video games in nation-building but not in nation-branding, in contrast with TV. This study presents a discussion of the findings to shed light on the cultural effects of video games.
Keywords: 1-Jeux vidéo; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À nettoyer; _À vérifier-Télé

From Separation to Integration: Identity Development of Korean Adult Players in Online Game World - Doh, Young Yim; Whang, Sang-Min Leo (Games and Culture, 2014)
This research examined the identity development of Korean adult players in the online game world. Q methodology was used to investigate the subjectivity of self-development in Mabinogi (Massive Multiplayer Online Role-Playing Game). Thirty-seven adult players sorted 57 behavior statements to reflect the changes in their behaviors from past to present. Three types of self-development were found: achievement-oriented development, control-oriented development, and relational development. The behavior patterns of these three types were compared to identify similarities and differences among them in terms of psychological meanings and values in the online game life. The results illustrate that the online game world can be defined as a new behavioral setting, made possible by digital technology, in which individuals are able to experience three different paths of identity development.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Japanese Console Games Popularization in China: Governance, Copycats, and Gamers - Liao, Sara X. T. (Games and Culture, 2016)
This article attempts to explore the popularization of Japanese console games in China in the past two decades, which reveals the tripartite relationship of the nation-state, transnational cultural power, and local agents.1 This study focuses on the formation and development of the console game industry in a non-Western context, where the society has undergone dramatic transformations and has been largely influenced by the globalization process. Encountering social anti-gaming discourse and cultural protectionism, the importation and distribution of Japanese console games did not get support from the state. However, it found its way to the audience and gained popularity through piracy, the black market, and the local agents’ appropriation, becoming an integrated part of many Chinese early gamers’ lives. This article draws upon the intersection of cultural globalization with game studies, calling for an investigation into the complexity of the game industry through its sociohistorical, political, and cultural environment.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Critical Cultural History of Online Games in China, 1995–2015 - Chew, Matthew M. (Games and Culture, 2016)
This study critically assesses the Chinese online games industry through problematizing the creativity of Chinese games. I find that between 1995 and 2001, Chinese online games were mostly developed by amateurs, noncommercial, and considerably creative. Between 2002 and 2005, industrial growth allowed some room for local creativity despite commercialization and dominance of imported games. Current scholarly, business, and media discourses unfairly ignore creativity in these first two periods and yet praise the Chinese game industry’s commercial success since the late 2000s. I challenge these discourses by illustrating that between 2006 and early 2009, a new, ethically dubious, and uniquely Chinese business model emerged, became domestically dominant, and quietly and profoundly impacted on global online game design. From mid-2009 to 2015, there is ongoing corporatization based on the dubious Chinese business model on the one hand, and a reemphasis on creativity motivated by browser and mobile game formats on the other.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games With a Continuum: Globalization, Regionalization, and the Nation-State in the Development of China’s Online Game Industry - Jiang, Qiaolei; Fung, Anthony Y.H. (Games and Culture, 2019)
As a case study, this article examines the development of China’s online game industry and how China responds to the forces of globalization. Based on in-depth interviews, ethnographic research, and the analysis of archive documents from the past few years, this study identifies China’s evolving strategy of neo-techno-nationalism. In the Chinese context, this national strategy manipulates technology to create a version of popular nationalism that is both acceptable to and easily censored by the authorities. Therefore, cultural industries that adopt this strategy stand a good chance of prevailing in the Chinese market. This success explains why the regional competitors of Chinese online games—Korean games—are more successful in China than most of their Western counterparts. By providing a snapshot of the current ecology of China’s online game industry, this article also discusses the influence of regional and global forces in a concrete context and argues that the development of China’s online game industry depends more on political factors than economic factors.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Balancing Gender Identity and Gamer Identity: Gender Issues Faced by Wang ‘BaiZe’ Xinyu at the 2017 Hearthstone Summer Championship - Schelfhout, Sam; Bowers, Matthew T.; Hao, Y. Andrew (Games and Culture, 2021)
This article examines a terrain in which gender inclusion remains a challenge: competitive esports. In the male-dominated sphere of esports, the underrepresentation of women and nonbinary people often leaves these marginalized groups invisible, with a significant lack of women and nonbinary people competing in top-tier tournaments. We highlight the experience of Wang ‘BaiZe’ Xinyu, a Chinese Hearthstone player who became the first woman to compete in a Hearthstone Championship Tour event in the game’s 3-year history. The narrative surrounding BaiZe’s participation largely focused on her gender and ignored the achievements that led her to qualify for the event. We argue that BaiZe’s entrance to the championship scene was received negatively by both competitors and spectators, reinforcing barriers that exclude women and nonbinary people from entering this male-dominated space. The discrimination faced by these esports competitors reinforces sexism inherent not only in Hearthstone but also in esports in general.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

“I Can be Who I Am When I Play Tekken 7”: E-sports Women Participants from the Islamic Republic of Pakistan - Hussain, Umer; Yu, Bo; Cunningham, George B.; Bennett, Gregg (Games and Culture, 2021)
Extant research on e-sports has focused on the growth and value of the phenomenon, fandom, and participant experiences. However, there is a paucity of e-sports scholarship detailing women’s experiences from marginalized communities living in various conservative Muslim countries. This shortage of literature remains despite different radical Islamic groups’ consistent demand for banning several online video games and the Muslim youth’s resistance to these calls. This study aimed to understand the motives and lived experiences of Muslim women e-sports participants from Gilgit-Baltistan, Pakistan. The authors collected data via observations of online video games and in-depth interviews. The study participants revealed that they use e-sports as a vehicle for an oppositional agency and personal freedom from the patriarchal system. The findings also suggest that participants are facing systematic marginalization and grave intrusion of post-colonization. The study contributes to the limited scholarship concerning Indian subcontinent Muslim women’s e-sports participation.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Décentrer l’histoire du jeu vidéo ? - Derfoufi, Mehdi (De l'autre côté, 2018)
Peut-on envisager une autre histoire du jeu vidéo ?
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Paradoxale légitimation culturelle du jeu vidéo - Derfoufi, Mehdi (De l'autre côté, 2019)
Qualifié parfois de « dixième art », après que les jeux de rôles sur table (comme Donjons & Dragons) eurent commencé à céder du terrain dans les loisirs de la jeunesse à partir du mil…
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Racisme et jeu vidéo - Derfoufi, Mehdi (Éditions de la Maison des sciences de l'homme, 2021)
En 2007, le monde du jeu vidéo est secoué par une violente polémique au sujet du jeu vidéo Resident Evil 5. Ce dernier est accusé de faire commerce du racisme, en invitant à se glisser dans la peau d'un américain blanc body-buildé, missionné dans une région africaine anonyme, et tuant des dizaines d'hommes et de femmes noires présentées comme de dangereux zombies infectés du virus T. Depuis, la communauté des joueurs et joueuses de jeux vidéo interpelle régulièrement les créateurs et créatrices des jeux sur les questions du racisme et du sexisme.Dans son ouvrage, Mehdi Derfoufi analyse les rapports de force qui structurent l'industrie du jeu vidéo, dévoilant comment le racisme se niche parfois insidieusement au cœur de scénarios de jeux vidéo à succès. Il nous invite à nous questionner. Quels sont les pays qui pèsent sur les milliards d'euros du marché mondial du jeu vidéo ? Qui sont les game designers et auteurs des jeux ? Comment les représentations racistes sont-elles véhiculées à travers les personnageset les imaginaires vidéoludiques ? L'auteur nous dévoile avec brio les logiques racialisantes à l’œuvre au sein d’un marché économique très concurrentiel où des stéréotypes exotisants servent régulièrement à faire vendre un jeu. Il nous montre aussi comment la division internationale du travail et la hiérarchie économico-politique Nord/Sud pèse sur le marché du jeu vidéo et ralentit l’émergence de nouvelles représentations. Pourtant, de nombreux espoirs, notamment dans les pays du Sud participent au renouvellement de la culture geek : face aux violences racistes, la riposte s’organise.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

‘‘When Keeping it Real Goes Wrong’’: Resident Evil 5, Racial Representation, and Gamers - Brock, André (Games and Culture, 2011)
Videogames’ ability to depict cultural iconographies and characters have occasionally led to accusations of insensitivity. This article examines gamers’ reactions to a developer’s use of Africans as enemies in a survival horror videogame, Resident Evil 5. Their reactions offer insight into how videogames represent Whiteness and White privilege within the social structure of ‘‘play.’’ Omi and Winant’s (1994) racial formation theory notes that race is formed through cultural representations of human bodies organized in social structures. Accordingly, depictions of race in electronic spaces rely upon media imagery and social interactions. Videogames construct exotic fantasy worlds and peoples as places for White male protagonists to conquer, explore, exploit, and solve. Like their precursors in science fiction, fantasy, and horror, videogame narratives, activities, and players often draw from Western values of White masculinity, White privilege as bounded by conceptions of ‘‘other,’’ and relationships organized by coercion and domination.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge Companions, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Don't Hate the Player, Hate the Game: The Racialization of Labor in World of Warcraft - Nakamura, Lisa (Critical Studies in Media Communication, 2009)
This article examines the racialization of informational labor in machinima about Chinese player workers in the massively multiplayer online role playing game World ofWarcraft. Such fan-produced video content extends the representational space of thegame and produces overtly racist narrative space to attach to a narrative that, whilecarefully avoiding explicit references to racism or racial conflict in our world, is premised upon a racial war in an imaginary world*the World of Azeroth. This profiling activityis part of a larger biometric turn initiated by digital culture’s informationalization of thebody and illustrates the problematics of informationalized capitalism. If late capitalism ischaracterized by the requirement for subjects to be possessive individuals, to make claims to citizenship based on ownership of property, then player workers are unnatural subjects in that they are unable to obtain avatarial self-possession. The painful paradox of this dynamic lies in the ways that it mirrors the dispossession of information workers in the Fourth Worlds engendered by ongoing processes of globalization. As long as Asian ‘‘farmers’’ are figured as unwanted guest workers within the culture of MMOs, user-produced extensions of MMO-space like machinima will most likely continue to depict Asian culture as threatening to the beauty and desirability of shared virtual space in the World of Warcraft.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Lyrical Nationalism: Gender, Friendship, and Excess in 1970s Hindi Cinema - Jha, Priya (The Velvet Light Trap, 2003)
In this essay I examine one particular feature of the films, the song-and-dance sequences, as they draw attention to the fractious nature of the postcolonial nation while simultaneously attempting to construct a space for the articulation of a consolidated national identity.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Games Studies India Adda Talk #9: Lakshmi Menon - Game Studies India Adda (Game Studies India Adda, 2021)
Unreal City: Expressions of Tokyo in Video Games Abstract: Games today, with advancements in graphic design and capability of the platforms on which they can be played, are almost akin to interactive films- in which the player not only consumes the movie-like storyline, but becomes an active participant in the narrative and its outcomes. Worldbuilding in video games has strong connections with the approaches contained in semiotics, as it is not with the images on the screen that players interact, but rather the world that is represented by the images. I intend to examine Tokyo as a virtually constructed game world in three separate texts – Atlus Studios’ Persona 5, Sega’s Yakuza series and Square Enix’s The World Ends with You. The fictionally created cityscapes of contemporary Japan have become ideal spaces for the video games to propagate, their construction in the texts can be seen a form of techno-orientalism that is simultaneously rooted in both Eastern and Western imagination. Each of these texts constructs its own version of Tokyo that, while being recognisable through the use of specific semiotic markers, is also sufficiently different enough to make it a virtual, unreal, space. However, what must be noted is that this space only exists in its entirety when it is interacted upon by the player. Using Lefebvre’s conceptualisation of social space into spatial practice, representations of space and representational space, this paper seeks to look at how the construction of the digital city is not merely a 3D representation thereof, but points where interactivity and narrative coincide. It is through the locus of these two elements that the player comprehends and navigates game narratives. My purpose will therefore be to look at the constructions of Tokyo within video games as data visualisations of spaces that become places through interactivity and comprehension of the player. About Laxmi: Lakshmi Menon is Assistant Professor of English at VTM NSS College, Trivandrum, and a PhD candidate at the Centre for English Studies, Jawaharlal Nehru University, where her thesis is a study of Harry Potter slash fanfiction and fan communities. She is currently researching Boys Love fan cultures in South Asia, while her wider research interests also include digital humanities, popular culture and queer literature.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Game Studies India Adda Talk #8: Prabhash Tripathy - Game Studies India Adda (Game Studies India Adda, 2021)
What/Who is playing Cyborg: An investigation of the 'Gamer' as a figure - Prabhash Ranjan Tripathy The current talk is an exploration into the question as to whether the gamer figure that emerged in India in the 1990s can be thought of as a cyborg and if so, then what kind of cyborg is the gamer? Can one think of the gamer-cyborg as a posthuman liberatory figure or is the gamer-cyborg still all too human? The intent of the paper in asking these questions and problematizing the figure of the Gamer is to launch an investigation into the more pressing question that one encounter in the wake of the cyber/information-turn, that is, how does one contemplate, comprehend, and articulate the 'new' in the identities that are formed and acquired with the advent of what has been identified as the cyber/information turn in culture? Can the connection between biological and technological be the sole basis for considering figurations like the Gamer as something new? Can they be thought of as a new subjectivity, a new politics, a new relationship to power? Is this 'new' democratic, free of discrimination and based on an egalitarian principle or is the 'new' an optimization of old and existing structures and modes of oppression? Bio: Prabhash Ranjan Tripathy was born in Odisha, India. He completed his B.A. (Hons) English, M.A. in English literature and M.A. in Comparative Indian Literature from University of Delhi. He is currently a PhD scholar at the school of Arts and Aesthetics, Jawaharlal Nehru University. Has submitted his MPhil dissertation titled ‘Playing Cyborg: A study of the Gamer in the Videogame Parlours of Delhi and Mussoorie’, following which was a doctoral fellow at the International Research Centre “Interweaving Performance Cultures” and is currently working on his PhD dissertation titled ‘Between WorkStation and PlayStation: The Cultural Location of Videogames in India’. Interest areas include Superhero comic books, Anime, Video Games, Combat Sports, and Mythology. He is fascinated by felines and loves to trek, read, write, click and play.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #3 The vanishing Curator - Game Studies India Adda (Game Studies India Adda, 2020)
Playing back to the Empire, in videogames, is rife with tensions. The imperialist sentiment inherent in reverse-colonist discourse featured in most strategy-based videogames like Europa Universalis IV, where the player could conquer Europe playing for the Marathas, has been noted by Souvik Mukherjee (2017) as playing into the colonial logic while futilely trying to challenge it. Studio Oleomingus, an Indian two-man game studio, is one of the few involved in a different experiment. Their mythical game Somewhere, chronicling a postmodernist search for identity and narrative in the forgotten city of Kayamgadh, has generated significant spin-offs into its universe. With attention to one such spin-off, I will focus critical attention on the issue of the postcolonial gaming of the Museum in A Museum of Dubious Splendors. I will examine the New Museological implications of A Museum of Dubious Splendors, keeping in mind Museologist Eilean Hooper-Greenhill’s assertion of museums embodying “the power to name, to represent common sense, to create official versions, to represent the social world, to represent the past” (Hooper-Greenhill 2001: 2). Oleomingus’ own description of A Museum, as an adaptation of edited, mangled, contested short stories by a fictional Urdu writer, Mir Umar Hassan, eschews the linear narrative production of the colonial museum for a game of meanings, where the player enters rooms according to his choice and constructs his/her own “quiet game about prosaic objects and spurious histories.” ("A Museum" 2018) The paper would take this into account and examine the reconceptualization of the museum space with respect to James Clifford’s sense of museums being “contact zones”: A Museum’s lack of any curator, with its curious blend of colonial and native tales and banal objects defamiliarised by “spurious histories” lends itself to questions of playing the Empire back according to a different episteme, through subaltern histories that the colonial museum space silenced. Paying close attention to the question of postcolonial spatiality in this game, I will analyze the historiographical implications of these identity-scatterings and recuperations at constant play in the structure of the game. Keywords: Museum Studies, Thing Theory, Game studies, Marginal identity, Postcolonial Studies
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

GSI Adda Talk #2 Riko Banerjee What is it like to be a Gamer or pursue Game Studies in India? - Game Studies India Adda (Game Studies India Adda, 2020)
Video gaming is one of the most popular hobbies in the world, with the gaming industry grossing more revenue than the movie and the music industry combined. The estimated number of gamers across the whole world as of August 2020 is 2.7 billion, which is more than one-third of the world population. The benefits of gaming, as cited by numerous researchers, include a boost in confidence, improved cognitive abilities, stress relief, improved problem-solving skills, enhanced social skills among dyslexic kids, and among many others. Even though video gaming as a hobby and career is slowly getting recognition in India, majority of the population still scoff at the activity, shunning gamers and game researchers alike, citing out-of-context and sometimes even false media propaganda. The challenges faced by a typical gamer in India include lack of information, budget limitation, lack of support from parents and teachers when it comes to teenage gamers, and the overall lack of gaming as a mainstream culture among countrymen. As for someone who wants to pursue Game Studies, there is currently little to no provision for that due to the tightly knit education system in the country and the utter lack of educational institutes offering courses on game studies. We go on to further discuss all of the above challenges and experiences faced by a gamer or someone who wants to pursue game studies in India, in our detailed talk that is scheduled on November 21, 2020.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

First-Person Encounters #3: Prof. Xenia Zeiler - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we interview Xenia Zeiler, an associate professor of South Asian studies at the University of Helsinki, Finland. Her research is situated at the intersection of digital media, religion, and culture, with a focus on India and the worldwide Indian community.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #2: Satyajit Chakaborty - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our second podcast where we interview Satyajit Chakraborty, a game developer, game designer and researcher. He also founded Flying Robots Studios in 2012 and has made various unique games. Here he talks about his first experiences with gaming in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

First Person Encounters #1: A Game Studies India Adda Podcast - Game Studies India Adda (2020)
The First Podcast in a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Japanese Video Games and Comics in Singapore: Issues in Popularization, Localization and their Implications - Ng Wai-ming, Benjamin (N.D., 1999)
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Talk #12: Geoffrey Fernandez - Game Studies India Adda (Game Studies India Adda, 2021)
Counter-Hegemonic Representations of Japanese Cultural Icons in Sekiro Abstract: Through fictional or non-fictional narratives, media representations of the past communicate specific interpretations, which lets users negotiate the past's prospective meanings. Additionally, these cultural constructions of the past are produced and disseminated in the present. Hence, the existing hegemonic power relations influence the depiction and recognition of cultural communities in the construction of the past. Therefore, the approach to framing cultures in pop-culture representations becomes a preponderating factor in how people perceive such cultures and periods. Sekiro: Shadows Die Twice, at first glance, can be considered as a game that follows the same vein of exploiting the western craze for the ninja archetype, as seen in its predecessors like the Onimusha and Tenchu series. However, it takes a bold stance against the persisting ‘self-Orientalist’ framework by reclaiming the ninja myth from marketized exoticization. Borrowing from Said’s theory of Orientalism, I would first like to analyze the existing self-Orientalism in depicting and marketing Japanese cultural icons. I would then like to highlight how this game is not an exoticized cultural artefact and further discuss the implications of such a portrayal in the contexts of representation and authenticity. I conclude that by undercutting innate stereotypes and using inherently Japanese characters, the game reappropriates the agency to depict Japanese cultural icons, from a non-Oriental, non-exoticized viewpoint. Thus, Sekiro: Shadows Die Twice becomes a stand-out in the video game industry in this respect. Bio: Geoffrey Fernandez is a PhD candidate at the Department of Humanities and Social Sciences at the Birla Institute of Technology and Science Pilani, Pilani campus. His doctoral research examines the use of culture, mythology, and folklore in video games.
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Lure of Pokémon: Video Games and the Savage Mind - Nakazawa, Shin'ichi (Japan library, 2019)
From its humble beginnings as a video game launched in the mid-90s, Pokémon has become a global entertainment franchise, even reaching into the world via "augmented reality" with the mobile game Pokémon GO. In the work, Nakazawa Shinichi argues that the Pokémon worldview is the best contemporary example of Claude Lévi-Strauss's "savage mind" (la pensée sauvage), suggesting that computer games can often be viewed as attempts to reconnect the human unconscious with the true, hidden essence of nature.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Playing Subaltern: Video Games and Postcolonialism - Mukherjee, Souvik (Games and Culture, 2018)
The postcolonial has still remained on the margins of Game Studies, which has now incorporated at length, contemporary debates of race, gender, and other areas that challenge the canon. It is difficult to believe, however, that it has not defined the way in which video games are perceived; the effect, it can be argued, is subtle. For the millions of Indians playing games such as Empire: Total War or East India Company, their encounter with colonial history is direct and unavoidable, especially given the pervasiveness of postcolonial reactions in everything from academia to day-to-day conversation around them. The ways in which games construct conceptions of spatiality, political systems, ethics, and society are often deeply imbued with a notion of the colonial and therefore also with the questioning of colonialism. This article aims to examine the complexities that the postcolonial undertones in video games bring to the ways in which we read them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Digital Middle East: State and Society in the Information Age - Zayani, Mohamed (Oxford University Press, 2018)
In recent years, the Middle East’s information and communications landscape has changed dramatically. Increasingly, states, businesses, and citizens are capitalizing on the opportunities offered by new information technologies, the fast pace of digital transformations, and enhanced connectivity. These changes are far from turning Middle Eastern nations into network societies, but their impact is significant. The growing adoption of a wide variety of information technologies and new media platforms in everyday life has given rise to complex dynamics that beg for a better understanding. Digital Middle East sheds a critical light on continuing changes that are closely intertwined with the adoption of information and communication technologies in the MENA region. Drawing on case studies from throughout the Middle East, the contributors explore how these digital transformations are playing out in the social, cultural, political, and economic spheres, exposing the various disjunctions and discordances that have marked the advent of the digital Middle East.
Keywords: 1-Jeux vidéo; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 5-Auteur.rice PANDC; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Videogames and Post-Colonialism: Empire Plays Back - Mukherjee, Souvik (Palgrave MacMillan, 2017)
This book focuses on the almost entirely neglected treatment of empire and colonialism in videogames. From its inception in the nineties, Game Studies has kept away from these issues despite the early popularity of videogame franchises such as Civilization and Age of Empire. This book examines the complex ways in which some videogames construct conceptions of spatiality, political systems, ethics and society that are often deeply imbued with colonialism. Moving beyond questions pertaining to European and American gaming cultures, this book addresses issues that relate to a global audience ? including, especially, the millions who play videogames in the formerly colonised countries, seeking to make a timely intervention by creating a larger awareness of global cultural issues in videogame research. Addressing a major gap in Game Studies research, this book will connect to discourses of post-colonial theory at large and thereby, provide another entry-point for this new medium of digital communication into larger Humanities discourses.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Transnational Contexts of Culture, Gender, Class, and Colonialism in Play: Video Games in East Asia - Pulos, Alexis; Lee, S. Austin (East Asian popular culture, 2016)
This book examines the local, regional and transnational contexts of video games through a focused analysis on gaming communities, the ways game design regulates gender and class relations, and the impacts of colonization on game design. The critical interest in games as a cultural artifact is covered by a wide range of interdisciplinary work. To highlight the social impacts of games the first section of the book covers the systems built around high score game competitions, the development of independent game design communities, and the formation of fan communities and cosplay. The second section of the book offers a deeper analysis of game structures, gender and masculinity, and the economic constraints of empire that are built into game design. The final section offers a macro perspective on transnational and colonial discourses built into the cultural structures of East Asian game play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

The Playing Fields of Empire: Empire and Spatiality in Video Games - Mukherjee, Souvik (Journal of Gaming & Virtual Worlds, 2015)
As in historical accounts, empire in video games too is concerned with the acquisition of geographical space. Like the splash of red marking the stretch of the British Empire on Victorian world maps, video games that let one play at empire are also obsessed with stamping the imperialist authority of ‘your’ nation on their in-game maps. Video game empires too work on the necessary logic of spatial expansion connected with which is the necessity to remove the ‘fog’ which prevents the player’s ‘line of sight’ from accessing information about surrounding areas. The focus on cartography and surveying in British Raj India is a useful comparison. Although much scholarship exists around the representations of the spatiality of Empire in more traditional media, there is little that addresses the video game representations of Empire. This article is about the representation and experience of space in conceptions of Empire vis-à-vis in empire-building video games, as understood in terms of both cartography and the lived experience of space. It argues that although empire-building video games are largely framed within the western imperialist discourses, the very nature of gameplay itself challenges these set notions – in a way remediating the ambiguity and anxieties of the representations of empire and its spatial constructs in earlier media.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Critical Interpretation of a New “Creative Industry” in Turkey: Game Studios and the Production of a Value Chain - Binark, Mutlu; Bayraktutan, Günseli (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
In this chapter, the creation of a value chain during the process of digital games development in Turkey is discussed using a critical political economy approach. This study claims to be the first of its kind that intends to examine the topography of the digital game industry in Turkey and gives a brief history and describes the present status of digital games production in Turkey. All the components of a value chain, namely, the industrial structure and development process, publishing and licensing, distribution and marketing structure, labor force, legal regulations, and governmental policies will be considered in that order to map out the present topography of the industry. The final part of the study will deal with possible solutions for further development in the industry. At this point, the study stresses the fact that all components of the value chain must be performed uninterrupted if the actors in Turkey’s digital game industry desire to position themselves as “producers” in global or local markets.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Egoshooting in Chernobyl: Identity and Subject(s) in the S.T.A.L.K.E.R. Games - Mukherjee, Souvik (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
The issue of identity formation when playing an avatar in a video game has recently become perceived as both increasingly complex and contentious. Game critics argue both for and against the apparent seamlessness in the identity formation in video games. However, while the case against seamlessness builds up with respect to other gaming genres, first-person shooters (FPS) are often still singled out as best representing this first-person identification whereby players were supposed to be totally immersed in their avatars while they played the game. In the light of recent research, this chapter builds on earlier research to reveal further problems in assuming a seamless merging of identity even in the FPS. It argues that the very conception of subjectivity has always been problematized through the FPS, and that the genre itself self-consciously keeps pointing this out. As an example of the latter, the chapter focuses on the S.T.A.L.K.E.R. video games to show how FPS games prompt players to question their in-game identity(ies) because the playing subject, instead of being a fixed entity, is hard-wired into the process of exploration that constitutes gameplay.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Beautiful Fighting Girl - Saitō, Tamaki; Azuma, Hiroki (University of Minnesota Press, 2011)
From Nausicaa to Sailor Moon, understanding girl heroines of manga and anime within otaku culture.
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge studies in new media and cyberculture, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Creative Industries Across Cultural Borders: The Case of Video Games in Asia - Tschang, Ted (Creative Economies, Creative Cities: Asian-European Perspectives, 2009)
This chapter examines the relationship between culture, economics and policy within the creative industries (which for the purposes of this paper, are assumed to be equivalent to the cultural industries), and their manifestation in Asia. Addressing any one of these three issues is a challenge in itself, but addressing all three of them together raises the complexity even further. Early writers on the “creative economy” have noted how it works differently from the traditional economy (Florida 2002; Howkins 2001).1 Culture is vitally important to understanding how creative industries develop, but the role of culture in shaping national competitive advantage is not that clear. The same can be said for policy, and a discussion of the triad can be quite convoluted. Having said that, all three levels are still very relevant to the proper description of a creative industry — as I will show in this chapter.This paper attempts to address this triad of issues primarily with a production-and-innovation-oriented view of industrial organisation, bringing in creativity, culture and policy where possible. I shall do this primarily through the lens of one sector in particular — the video games industry — in which Asia has been investing heavily lately, and in which Japan has been an early leader. I will also provide a limited focus on the animation sector for comparative purposes. I will first provide a summary of how creative production in video games occurs in the US, followed by an examination of how Asian patterns compare. In particular, I am interested in whether individual and industrial level creativity differs in Asia. Within Asia, more detailed cases of the Chinese online games industry and the Philippine animation industry will be discussed, but relevant observations are also drawn from general knowledge and a literature review of Japan, Korea and Singapore, as well as interviews which corroborate those observations.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games in Asia - Ng Wai-ming, Benjamin (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

ゲーム的リアリズムの誕生 ; Gēmu-teki riarizumu no tanjō - Azuma, Hiroki (Dōbutsukasuru posutomodan, 2007)
Keywords: 1-Jeux vidéo; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer

Japanese Video Games in Singapore: History, Culture and Industry - Ng Wai-ming, Benjamin (Asian Journal of Social Science, 2001)
Globalization of Japanese popular culture is reshaping the global cultural landscape. Some forms of Japanese popular culture (such as video games animation and sushi) are well-received internationally, whereas others (such as pop music, films and TV dramas) are only popular in Asia. Of all forms of Japanese popular culture, video game is perhaps the most powerful due to its strong universal appeal. It has dominated the world market since the mid-1980s. This article uses Singapore as a case study to demonstrate the global popularization of Japanese video games. There has been a boom of Japanese popular culture in Singapore in the 1990s. In particular, Japanese video games, comics and animation have become an integral part of youth culture in Singapore (Ng, March 2000: 234-246; Ng, May 2000: 44-56; Ng, June 2000: 1-14). Video game is a neglected topic in cultural studies. Although there are some basic studies of Japanese video games in the Western world (Hayes & Disney, 1995; Herz, 1997; Kinder 1991; Monopolies, 1995; Sheff, 1993), its impact in Asia is largely unknown. This article is a preliminary study of the Japanese video game culture and industry in Singapore from historical and socio-cultural perspectives, focusing on consoles, games and players. Based on interviews, questionnaires and data from newspapers and magazines, this research aims at pro viding a general overview of the history and impact of Japanese video games in Singapore. All the data and analyses are basic and this is beyond the scope of this paper to discuss any particular issue or theory in details. This paper consists of four sections. The first three sections outline the development of home video game consoles, handheld electronic games and game arcades respectively. The concluding section pinpoints the characteristics of the video
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

電脳遊戯の少年少女たち ; Dennō yūgi no shōnen shōjotachi - Nishimura, Kiyokazu (Kōdansha gendai shinsho, 1999)
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer